The role of digital activism within social movements to foster democratization in the global south: the case of Ni Una Menos - Dias Rohm, Ricardo Henry; de Souza Valuano, Gabriel; Ferreira Xavier, Sofia de Souza (Espacio Abierto, 2023)
The present paper aimed to describe how social movements in the Global South can use digital technologies to seek the promotion of democratization. A mixed approach was applied to a case study, combining the use of simple statistical frequency with the content analysis technique to categorize texts, images and sounds on the Ni Una Menos’ Instagram page. Based on Sen’s (2000) instrumental freedoms, the modalities of Rohm, Xavier and Valuano’s analytical model (forthcoming) and on the criteria of quality of communication, media type and engagement outlined on the present paper, the impacts and contributions of the use of digital technologies by social movements for democratization in the Global South were discussed. Finally, the results demonstrate that most of the publications analyzed had the purpose of sensitizing or organizing NUM’s public, consisting of 99.6% of the posts. The most important media were arts (33.42%) and photographs (41.88%), followed by videos (18.72%). The quality of communication did not stand out as a determining factor of the generated engagement, which suggests a limitation of the social media used for the movement’s intended purposes.